PERBEDAAN KADAR PM2,5 DI TEMPAT PEMBAKARAN BATU BATA DAN KEJADIAN SINDROMA MATA KERING - Nur Rohmawati; Retno Andriyani (The Indonesian Journal of Occupational Safety and Health, 2018)
Brick cumbustion in Kaloran Village uses firewood and corncob as main fuel. Combustion using firewood and corncobs in  burning bricks produce PM2.5 pollutants that can cause health problem including the eyes. Dry eye is a multifactorial disease of ocular surface in symptoms that include discomfort, visual disturbance and tear film instability with potential damage to the ocular surface. This study aims to describe PM2.5 levels in brick combustion and dry eye syndrome events in brick workers in Kaloran Village Ngronggot Nganjuk District in 2017. This research was an observational study with cross sectional design, conducted in May 2017, Using questionnaires, interviews and observations with a large sample of 42 respondents. The PM2.5 measurements use the Haz-Dust EPAM 5000 model for 30 minutes, which is performed three times a day at each point of location. Data collection on the incidence of dry eye syndrome was diagnosed using an OSDI questionnaire. All measurements of PM2.5 exceed the ambient air quality standard of government regulation number 41 of 1999 of (0.065 mg/m3) and There are three measurement result of PM2.5 that exceed the Threshold Limit No 13 of 2011 about Threshold Value of Physical Factors and Chemical Factors in the Work Environment. There are 71.6% workers experience dry eye syndrome. In the results of this study, PM2.5 levels are in place. The advantages and disadvantages of some places that exceed the Threshold Limit and there are workers who experience dry eye syndrome. Keywords: burning bricks, dry eye syndrome, level of  PM2,5